Fractais no ensino médio - Brisante, Ilca Maria [UNESP] (2013)
The purpose of this work is to provide some activities to be developed in the classroom with students from basic education, involving geometric fractals. The characterization of these objects is made through two of its main features: self-similarity and its dimension not necessarily entire, which enables the approach to issues such as numerical sequences and notions of limits with high school students. Such activities may also be used as a supplement to lessons of arithmetic and geometric progressions, logarithms and area of equilateral triangles